(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article raises a scientific problem regarding the need to introduce innovative pedagogical technologies into the educational process of out-of-school educational institutions. The use of innovative pedagogical technologies in out-of-school education is revealed on the example of the Kirovohrad Regional Center for Children’s and Youth Creativity. The experience of the innovative pedagogical technology "Art - the laboratory of life tasks" is highlighted. The stages of formation of innovative pedagogical technology are characterized. The thematic directions of the specified Art-Laboratory are outlined, in particular: Take care of the health of youth: traditions of the Ukrainian family - a valuable inheritance for a child; artist and citizen: ways of combination; I and the Universe; there is always a place for a feat in life; spiritual intelligence throughout life, etc. The work with the students according to the thematic directions of Art - laboratory of life tasks is described, in particular the purpose, methods and forms of organizing classes. The duration of classes on the proposed topics of the thematic laboratories is 45 minutes and is conducted according to the frontal and group forms of organization of classes. According to the teaching staff of the Kirovohrad Regional Centre of Childrens and Youth Creativity, the following innovative forms of working with students are effective: mini-lecture, class-discussion, game training, thematic discussion, express travel, game-conversation, dramatization, solving problem situations, video quiz, "Brain assault", "Openwork saw", "Diamond ranking", SWOT analysis, etc. The form of working with students "Diamond ranking" is disclosed in more detail. It was concluded that the innovative pedagogical technology developed and implemented by the team of the Kirovohrad Regional Centre of Childrens and Youth Creativity contributes to the formation of the necessary spiritual, moral and patriotic qualities in the younger generation.